Preparation method of zinc sulfide optical transparent ceramic

By directly hot-pressing the cubic β-ZnS nanopowder and adding alkali metal halide salt and metal sulfide as additives, the problem of low-temperature phase transition inducing nanoscale is solved, and high-performance pure cubic structure zinc sulfide transparent ceramics are prepared.

CN119638426APending Publication Date: 2025-03-18晋琳雅
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878572.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, when using nano-scale cubic structure β-ZnS powder to prepare zinc sulfide transparent ceramics, there is a problem of nano-size-induced low-temperature phase transition, resulting in the prepared ceramics containing hexagonal wurtzite α-ZnS heterophase, affecting their optical and other properties.

Method used

The cubic β-ZnS nanopowder is used as raw materials and directly sintered by hot pressing. By adding alkali metal halide salt and metal sulfide as additives, the molecular layer coating is formed on the surface of β-ZnS nanoparticles to improve the phase stability of the nanoparticles and avoid low-temperature phase change.

Benefits of technology

The zinc sulfide optical transparent ceramic with pure cubic structure β-ZnS phase without hexagonal phase was prepared, which improved the optical and other properties of the ceramics. It has simple process, short sintering time, high efficiency, low energy consumption and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638426A_ABST
    Figure CN119638426A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of zinc sulfide optical transparent ceramic, and belongs to the technical field of new materials. The preparation method comprises the following steps: weighing beta-ZnS nano-powder of a cubic sphalerite crystal phase as a raw material; preparing an alkali metal halide salt additive and a metal sulfide additive; mixing the weighed raw materials with the two additives to prepare precursor powder of the zinc sulfide transparent ceramic; the mass ratio of the alkali metal halide salt additive is 3.0 wt.%-7.0 wt.% of the total mass of the beta-ZnS nano powder; the mass ratio of the metal sulfide additive is 0.0 wt.%-5.0 wt.% of the total mass of the beta-ZnS nano powder; and putting the precursor powder of the zinc sulfide transparent ceramic into a high-temperature sintering mold, carrying out hot pressed sintering in a vacuum environment or a protective gas environment, and cooling to obtain the zinc sulfide infrared optical transparent ceramic without the hexagonal wurtzite crystal phase. According to the invention, the problem that the nano-size of the nano beta-ZnS powder induces low-temperature phase change is solved, and the zinc sulfide transparent ceramic prepared by hot pressing does not contain hexagonal sphalerite alpha-ZnS impure phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and in particular relates to a method for preparing zinc sulfide optically transparent ceramics. Background Art

[0002] Zinc sulfide (ZnS) is an important II-VI semiconductor material, which usually exists in two crystal phases, namely, the sphalerite crystal phase (i.e., β-ZnS phase) and the wurtzite crystal phase (i.e., α-ZnS phase); among them, the sphalerite crystal phase is a stable phase at room temperature, and the corresponding unit cell structure is face-centered cubic; the wurtzite crystal phase is a high-temperature stable phase, and the corresponding unit cell structure is a hexagonal crystal structure; under a standard atmospheric pressure, the cubic structure β-ZnS phase will undergo a solid-state phase transition at 1020°C to transform into a hexagonal structure α-ZnS phase. Generally speaking, cubic zinc sulfide has more important technical uses. Its bandgap is 3.72eV, and it is a typical II-VI wide bandgap semiconductor and an important optoelectronic functional material. Since cubic crystals do not have birefringence and are optically isotropic, cubic β-ZnS polycrystalline transparent ceramic materials have excellent optical properties. Its optical transmission band is 0.4-14.6μm, and the light transmission band covers visible light (0.4-0.75μm), short-wave infrared (1.0-3.0μm), medium-wave infrared (3-5μm) and long-wave infrared (8-12μm) bands. It has outstanding mechanical, thermal and physical and chemical properties and is an excellent multi-spectral infrared wave-transmitting material. It can be widely used in windows and optical components of infrared imaging, infrared detection and infrared optical communication systems.

[0003] At present, the main technologies for preparing zinc sulfide polycrystalline transparent ceramics are hot pressing (HP) and chemical vapor deposition (CVD). Among them, the CVD method has complex equipment requirements, a long preparation process, high toxicity of the reaction gases such as hydrogen sulfide used, and prominent environmental protection issues, resulting in high cost and poor mechanical properties of CVD-ZnS transparent ceramics. Zinc sulfide transparent ceramics with excellent mechanical properties are all prepared by hot pressing. The raw materials currently used are mainly micron-scale cubic β-ZnS powders for hot pressing and sintering. However, there are still many technical problems in using nano-scale cubic β-ZnS powders as raw materials to prepare ZnS transparent ceramics by hot pressing. For example, the existing technology uses nano-sized cubic β-ZnS powders as raw materials, and there is an obvious size-induced low-temperature phase transition. The nano-size induced phase transition depends on the size of the nanocrystals and can be sintered at a temperature of about 1000. The phase transition temperature of β-ZnS particles with a size of 10 to 15 nm can be reduced to about 400°C, which is much lower than the phase transition temperature of 1020°C when the cubic phase of zinc sulfide body crystals transforms into the hexagonal phase, and is also significantly lower than the sintering temperature of zinc sulfide ceramics, such as 850°C to 1050°C. This results in the zinc sulfide transparent ceramics sintered with cubic nano-β-ZnS powders always containing hexagonal wurtzite α-ZnS impurities, which is not conducive to the application performance of zinc sulfide transparent ceramics. 2 Under the protection of S gas, nano powder raw materials are heat treated at high temperature to increase their particles to submicron or micron level, and then hot pressing technology is used to prepare zinc sulfide transparent ceramics. The defects of this technology are: first, the processing time of nano powder raw materials is long and the energy consumption is high; second, part of nano β-ZnS powder can form hexagonal α-ZnS particles through low-temperature phase transformation during the heat treatment process; third, it is difficult to completely increase the particle size of β-ZnS nano powder to submicron or micron level during the heat treatment process; fourth, powders that fail to grow into submicron size through heat treatment still form hexagonal heterophase or secondary phase through phase transformation during sintering; the above technical defects result in the presence of hexagonal phase in the zinc sulfide transparent ceramics finally prepared by hot pressing, which has a serious negative impact on the optical and other properties of ZnS transparent ceramics. Summary of the invention

[0004] Technical issues to be solved:

[0005] In order to avoid the shortcomings of the prior art, the present invention provides a method for preparing zinc sulfide optically transparent ceramics, which uses cubic β-ZnS nanopowder as a raw material, directly hot-presses and sinters the nanopowder, and prepares pure cubic crystal phase zinc sulfide optically transparent ceramics. The technology does not require heat treatment of the nano β-ZnS powder raw material, and can overcome the problem of nano-size-induced low-temperature phase transition of nano β-ZnS powder. The zinc sulfide transparent ceramics prepared by hot pressing do not contain hexagonal sphalerite α-ZnS impurity phase.

[0006] The technical solution of the present invention is: a method for preparing zinc sulfide optically transparent ceramics, the specific steps are as follows:

[0007] Weighing β-ZnS nanopowder in cubic sphalerite crystal phase as raw material;

[0008] Formulating alkali metal halide salt additives and metal sulfide additives;

[0009] The weighed raw materials and two additives are mixed to prepare a precursor powder of zinc sulfide transparent ceramic; the mass proportion of the alkali metal halide salt additive is 3.0wt.% to 7.0wt.% of the total mass of the β-ZnS nanopowder; the mass proportion of the metal sulfide additive is 0.0wt.% to 5.0wt.% of the total mass of the β-ZnS nanopowder;

[0010] The precursor powder of zinc sulfide transparent ceramic is placed in a high-temperature sintering mold, hot-pressed and sintered in a vacuum environment or in a protective gas environment, and after cooling, zinc sulfide infrared optical transparent ceramics free of hexagonal wurtzite crystal phase are obtained.

[0011] A further technical solution of the present invention is that the average particle size of the cubic sphalerite crystal phase β-ZnS nanopowder is between 10 nm and 100 nm.

[0012] A further technical solution of the present invention is that the alkali metal halide salt additive is prepared by mixing one or more alkali metal halide salt powders, which are dried and then mixed and ground into a mixed powder having an average particle size of no more than 300 microns;

[0013] A further technical solution of the present invention is that the alkali metal halide salt is NaBr, NaI, KBr, KI, RbBr, or RbI.

[0014] A further technical solution of the present invention is that the metal sulfide additive is prepared by mixing one or more metal sulfide powders, which are dried and then mixed and ground into a mixed powder with an average particle size of no more than 10 microns.

[0015] A further technical solution of the present invention is: the metal sulfide is MgS, CaS, BaS, CaLa2S4, γ-La2S3 or NaLaS2.

[0016] A further technical solution of the present invention is: the specific process of hot pressing and sintering the precursor powder of the zinc sulfide transparent ceramic is as follows:

[0017] The precursor powder of zinc sulfide transparent ceramic put into the mold is placed in a hot pressing sintering high temperature furnace, and the vacuum degree of the furnace chamber is adjusted to 1.0-20.0 Pa, or argon gas with a flow rate of 30-100 ml / min, or nitrogen gas with a flow rate of 30-100 ml / min is introduced;

[0018] Applying a pressure of 30MPa to 200MPa to the precursor powder of zinc sulfide transparent ceramic in the mold;

[0019] The hot pressing sintering high temperature furnace is heated to 750°C to 950°C at a rate of 3 to 20°C / min and kept at this temperature for 0.5 to 3.0 hours;

[0020] After the heat preservation is completed, the pressure is removed, and after the hot pressing sintering high temperature furnace is naturally cooled to room temperature, the vacuum or Ar gas or nitrogen is removed;

[0021] The sample is taken out from the mold to obtain a hot-pressed bulk ZnS ceramic, which is polished to obtain a zinc sulfide infrared optically transparent ceramic free of hexagonal wurtzite crystal phase.

[0022] Disclosed is a zinc sulfide optically transparent ceramic, which is obtained according to a preparation method of the zinc sulfide optically transparent ceramic.

[0023] A further technical solution of the present invention is: the raw materials of the zinc sulfide optically transparent ceramic include β-ZnS nanopowder of cubic sphalerite crystal phase with an average particle size between 10nm and 100nm, and alkali metal halide salt additives and metal sulfide additives; the mass proportion of the alkali metal halide salt additive is 3.0wt.% to 7.0wt.% of the total mass of the β-ZnS nanopowder, and the mass proportion of the metal sulfide additive is 0.0wt.% to 5.0wt.% of the total mass of the β-ZnS nanopowder.

[0024] An application of zinc sulfide optically transparent ceramics. The zinc sulfide optically transparent ceramics are used as infrared wave-transmitting materials and can transmit long-wave infrared light in the 8-14 μm band.

[0025] Beneficial Effects

[0026] The beneficial effect of the present invention is that: the present invention adopts cubic sphalerite structure β-ZnS nanopowder as raw material, directly hot-presses and sinters the nano raw material, and can prepare zinc sulfide optically transparent ceramics of pure cubic structure β-ZnS phase without hexagonal phase. Compared with the existing zinc sulfide optically transparent ceramic sintering technology, the present invention uses cubic sphalerite structured β-ZnS nanopowder as raw material, and the additive 1 forms a molecular layer coating on the surface of the β-ZnS nanoparticles through surface solid-state molecular diffusion and melting during the sintering process, which greatly reduces the surface energy of the β-ZnS nanoparticles and improves the phase stability of the β-ZnS nanoparticles, so that there is no need to heat-treat the nano raw material to increase the particle size, effectively overcoming the nano-size induced low-temperature phase transition of the cubic structured β-ZnS nanopowder, and realizing the direct densification sintering of the cubic nano zinc sulfide powder; at the same time, the additive 2 applied has a higher melting point and difficult sintering than zinc sulfide, and can be aggregated at the grain boundary during the zinc sulfide sintering process to hinder the excessive growth of grains, so that it is easy to prepare zinc sulfide transparent ceramics with controllable particle size and high density. The scheme has the characteristics of simple process, short sintering time, high efficiency, low energy consumption and low cost. It is suitable for batch preparation of zinc sulfide optically transparent ceramics and has broad development and application prospects.

[0027] It has been verified by experiments. Figure 1 (a) and (b) show the X-ray diffraction (XRD) patterns of the typical β-ZnS nanopowder raw material and the hot-pressed zinc sulfide transparent ceramics, respectively. Figure 1 (a') (b') show the scanning electron microscopy (SEM) images of β-ZnS nanopowder raw material and zinc sulfide transparent ceramic, respectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 XRD patterns of typical samples: (a) β-ZnS nanopowder raw material, (b) hot-pressed zinc sulfide transparent ceramics; scanning electron microscopy (SEM) photos: (a') β-ZnS nanopowder raw material, (b') hot-pressed zinc sulfide transparent ceramics. DETAILED DESCRIPTION

[0029] The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0030] Based on the problem that the existing zinc sulfide transparent ceramics all have hexagonal phases, which have serious negative effects on the optical and other properties of ZnS transparent ceramics, the present invention provides a method for preparing zinc sulfide optically transparent ceramics, using cubic sphalerite nanopowder as a raw material, and directly hot-pressing a method for preparing pure cubic crystal phase zinc sulfide optically transparent ceramics, and the specific steps are as follows:

[0031] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0032] Take dried cubic sphalerite crystal phase β-ZnS nanopowder with an average particle size of 10 nm to 100 nm as a raw material, and weigh the total mass of the β-ZnS nanopowder.

[0033] Step 2: Additive treatment

[0034] One or more alkali metal halide salts are selected as additive 1, dried, mixed and ground into powder with an average particle size of no more than 300 microns. One or more metal sulfides are selected, dried separately, mixed and ground into mixed powder with an average particle size of no more than 10 microns as additive 2.

[0035] The alkali metal halide salt involved in step 2 refers to NaBr, NaI, KBr, KI, RbBr, and RbI.

[0036] The metal sulfides involved in step 2 are MgS, CaS, BaS, CaLa2S4, γ-La2S3, and NaLaS2.

[0037] When the additive 1 involved in step 2 is several alkali metal halide salts, the ratio between the alkali metal halide salts is arbitrary.

[0038] When the additive 2 involved in step 2 is several kinds of metal sulfides, the ratio between the metal sulfides is arbitrary.

[0039] Step 3: Preparation of zinc sulfide transparent ceramic precursor powder

[0040] Weigh a certain amount of the powder of the alkali metal halide salt prepared in step 2 as additive one; at the same time, weigh a certain amount of the powder of the metal sulfide prepared in step 2 as additive two, add all the weighed two additive powders to the weighed cubic sphalerite crystal phase β-ZnS nanopowder raw material in step 1, mix the three powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0041] The addition ratio of the alkali metal halide salt additive powder 1 involved in step 3 is 3.0wt.% to 7.0wt.% (mass percentage) of the total mass of the β-ZnS nanopowder; the addition ratio of the metal sulfide additive powder 2 is 0.0wt.% to 5.0wt.% (mass percentage) of the total mass of the β-ZnS nanopowder.

[0042] Step 4: Densification sintering of zinc sulfide transparent ceramics

[0043] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold and placed in a hot pressing and sintering high-temperature furnace, and then the vacuum degree of the furnace chamber is adjusted to 1.0-20.0Pa, or argon gas with a flow rate of 30-100ml / min, or nitrogen gas with a flow rate of 30-100ml / min is introduced, and then a pressure of 30MPa-200MPa is applied to the precursor powder, and then the hot pressing and sintering high-temperature furnace is heated to 750℃-950℃ at a rate of 3-20℃ / min, and the temperature is kept for 0.5-3.0 hours. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and the vacuum or Ar gas or nitrogen is removed; the sample is taken out from the mold to obtain a hot pressed block ZnS ceramic, which is polished to obtain a zinc sulfide infrared optical transparent ceramic without hexagonal wurtzite crystal phase.

[0044] The above technical solution is further described below with reference to examples and drawings:

[0045] Example 1: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0046] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0047] Take 25.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 10 to 20 nm.

[0048] Step 2: Additive treatment

[0049] Alkali metal halide salt KBr is selected, dried, and ground into powder with an average particle size of 0.5 to 5 μm as additive 1. Metal sulfides CaS and BaS are selected, and the two sulfides are mixed in equal proportions according to the amount of substance, dried, and ground into mixed powder with an average particle size of 50 to 90 nanometers as additive 2.

[0050] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0051] Weigh 1.0 g of the additive 1 powder ground in step 2, so that it accounts for 4.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; weigh 1.25 g of the additive 2 powder ground in step 2, so that it accounts for 5.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed two additive powders to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the three powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0052] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0053] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, placed in a hot pressing and sintering high-temperature furnace, the vacuum degree of the furnace chamber is adjusted to 1.0 Pa, and a pressure of 200 MPa is applied. Then, the hot pressing and sintering high-temperature furnace is heated to 750°C at a rate of 20°C / min, and the temperature is kept for 0.5 hours. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and then the vacuum is removed; the sample is taken out from the mold to obtain a hot pressed block ZnS ceramic, which is polished to obtain a zinc sulfide optically transparent ceramic that does not contain a hexagonal wurtzite crystal phase, and the average particle size of the prepared ceramic sample grains is about 95nm, and the average transmittance in the 8-14μm band is 56%.

[0054] Example 2: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0055] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0056] Take 30.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 70 to 100 nm.

[0057] Step 2: Additive treatment

[0058] Alkali metal halide salts NaBr and KI were selected, and the two halides were mixed in a molar ratio of 1:2, dried, and ground into powders with an average particle size of about 230 to 300 μm as additive 1. Metal sulfide CaLa was selected. 2 S 4 , and then dried and ground into powder with an average particle size of 8 to 10 microns as additive 2.

[0059] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0060] Weigh 1.8 g of the powder of the additive 1 ground in step 2, so that it accounts for 6.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; weigh 0.6 g of the powder of the additive 2 ground in step 2, so that it accounts for 2.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed two additive powders to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the three powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0061] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0062] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, and placed in a hot pressing and sintering high-temperature furnace. Argon gas with a flow rate of 100 ml / min is introduced into the furnace cavity, and a pressure of 30 MPa is applied. Then, the hot pressing and sintering high-temperature furnace is heated to 950°C at a rate of 3°C / min, and the temperature is kept for 1.0 hour. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and the argon gas is removed; the sample is taken out from the mold to obtain a hot pressed block ZnS ceramic, which is polished to obtain a zinc sulfide optically transparent ceramic free of hexagonal wurtzite crystal phase, and the average transmittance of the sample in the 8-14 μm band is 65%.

[0063] Example 3: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0064] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0065] Take 28.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 20 to 50 nm.

[0066] Step 2: Additive treatment

[0067] Alkali metal halide salts KBr, RbBr and RbI were selected, and the three halides were mixed in a molar ratio of 0.5:2:3, dried, and ground into powder with an average particle size of about 120 to 200 μm as additive 1. Metal sulfide CaLa was selected. 2 S 4 , and then dried and ground into powder with an average particle size of 0.2 to 0.5 microns as additive 2.

[0068] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0069] Weigh 1.96 g of the additive 1 powder ground in step 2, so that it accounts for 7.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; weigh 1.4 g of the additive 2 powder ground in step 2, so that it accounts for 5.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed two additive powders to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the three powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0070] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0071] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, and placed in a hot pressing and sintering high-temperature furnace. Nitrogen with a flow rate of 50 ml / min is introduced into the furnace cavity, and a pressure of 50 MPa is applied. Then, the hot pressing and sintering high-temperature furnace is heated to 850°C at a rate of 10°C / min and kept warm for 1.5 hours. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and then the argon is removed; the sample is taken out from the mold to obtain a hot pressed block ZnS ceramic, which is polished to obtain a zinc sulfide optically transparent ceramic free of hexagonal wurtzite crystal phase, and the average transmittance of the sample in the 8-14 μm band is 66%.

[0072] Example 4: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0073] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0074] Take 26.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 10 to 40 nm.

[0075] Step 2: Additive treatment

[0076] Alkali metal halide salt NaI is selected, dried, and ground into powder with an average particle size of about 50 to 100 μm as additive 1. Metal sulfides BaS, CaLa 2 S 4 and γ-La 2 S 3 , three kinds of sulfides are mixed in sequence according to the molar ratio of 3:1:0.5, and then dried and ground into powder with an average particle size of 0.8 to 1.0 microns as additive two.

[0077] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0078] Weigh 0.78 g of the powder of the additive 1 ground in step 2, so that it accounts for 3.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; weigh 1.3 g of the powder of the additive 2 ground in step 2, so that it accounts for 5.0 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed two additive powders to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the three powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0079] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0080] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, and placed in a hot pressing and sintering high-temperature furnace. Argon gas with a flow rate of 30 ml / min is introduced into the furnace cavity, and a pressure of 70 MPa is applied. Then, the hot pressing and sintering high-temperature furnace is heated to 830°C at a rate of 9°C / min and kept warm for 2.0 hours. After the insulation is completed, the pressure is removed. After the hot pressing furnace is naturally cooled to room temperature, the argon gas is removed. The sample is taken out from the mold to obtain a hot pressed block ZnS ceramic. After polishing, an optically transparent zinc sulfide ceramic free of hexagonal wurtzite crystal phase is obtained, and the average transmittance of the sample in the 8-14 μm band is 69%.

[0081] Example 5: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0082] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0083] Take 32.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 10 to 40 nm.

[0084] Step 2: Additive treatment

[0085] Alkali metal halide salt KBr is selected, dried, and ground into powder with an average particle size of about 110 to 160 μm as an additive.

[0086] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0087] Weigh 1.12 grams of the additive powder ground in step 2, so that it accounts for 3.5wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed additive powder to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the two powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0088] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0089] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, and placed in a hot pressing and sintering high-temperature furnace. Argon gas with a flow rate of 80 ml / min is introduced into the furnace cavity, and a pressure of 80 MPa is applied. Then, the hot pressing and sintering high-temperature furnace is heated to 860°C at a rate of 12°C / min, and the temperature is kept for 1.0 hour. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and the argon gas is removed; the sample is taken out from the mold to obtain a hot pressed bulk ZnS ceramic, and after polishing it, an optically transparent zinc sulfide ceramic free of hexagonal wurtzite crystal phase is obtained, and the average transmittance of the sample in the 8-14 μm band is 71%.

[0090] Example 6: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0091] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0092] Take 30.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 20 to 40 nm.

[0093] Step 2: Additive treatment

[0094] Alkali metal halide salt RbBr is selected, dried, and ground into powder with an average particle size of about 190 to 230 μm as an additive.

[0095] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0096] Weigh 1.5 grams of the additive powder ground in step 2, so that it accounts for 5.0wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed additive powder to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the two powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0097] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0098] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, placed in a hot pressing and sintering high-temperature furnace, nitrogen with a flow rate of 60 ml / min is introduced into the furnace cavity, a pressure of 100 MPa is applied, and then the hot pressing and sintering high-temperature furnace is heated to 900°C at a rate of 6°C / min, and the temperature is kept for 1.0 hour. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and then the nitrogen is removed; the sample is taken out from the mold to obtain a hot pressed block ZnS ceramic, which is polished to obtain a zinc sulfide optically transparent ceramic without a hexagonal wurtzite crystal phase, and the average transmittance of the sample in the 8-14 μm band is 69%.

[0099] Example 7: Preparation of transparent zinc sulfide ceramics from cubic β-ZnS nanopowder

[0100] Step 1: Weighing of cubic β-ZnS nanopowder raw materials

[0101] Take 30.0 grams of dried cubic sphalerite β-ZnS nanopowder with an average particle size of 50 to 90 nm.

[0102] Step 2: Additive treatment

[0103] Alkali metal halide salts NaBr, KBr and RbBr are selected, and the three halides are mixed in a molar ratio of 2:1:0.3, dried, and ground into powders with an average particle size of about 10 to 20 μm as additive 1. Metal sulfide MgS is selected, dried, and ground into powders with an average particle size of 1.0 to 2.0 μm as additive 2.

[0104] Step 3 Preparation of zinc sulfide transparent ceramic precursor powder

[0105] Weigh 1.65 g of the powder of additive 1 ground in step 2, so that it accounts for 5.5 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; weigh 1.35 g of the powder of additive 2 ground in step 2, so that it accounts for 4.5 wt.% of the mass of the β-ZnS nanopowder weighed in step 1; add all the weighed two additive powders to the β-ZnS nanopowder of cubic sphalerite crystal phase weighed in step 1, mix the three powders evenly, and obtain a precursor powder for preparing zinc sulfide transparent ceramics.

[0106] Step 4 Densification sintering of zinc sulfide transparent ceramics

[0107] The precursor powder of the zinc sulfide transparent ceramic prepared in step 3 is placed in a mold, placed in a hot pressing and sintering high-temperature furnace, the vacuum degree of the furnace chamber is adjusted to 1.0 Pa, and a pressure of 30 MPa is applied. Then, the hot pressing and sintering high-temperature furnace is heated to 900°C at a rate of 18°C / min and kept warm for 2.0 hours. After the insulation is completed, the pressure is removed, and the hot pressing furnace is naturally cooled to room temperature, and then the vacuum is removed; the sample is taken out from the mold to obtain a hot pressed block ZnS ceramic, which is polished to obtain a zinc sulfide optically transparent ceramic free of hexagonal wurtzite crystal phase, and the average transmittance of the sample in the 8-14μm band is 70%.

[0108] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A method for preparing zinc sulfide optically transparent ceramics, characterized in that The specific steps are as follows: Weighing β-ZnS nanopowder in cubic sphalerite crystal phase as raw material; Formulating alkali metal halide salt additives and metal sulfide additives; The weighed raw materials and two additives are mixed to prepare a precursor powder of zinc sulfide transparent ceramic; the mass proportion of the alkali metal halide salt additive is 3.0wt.% to 7.0wt.% of the total mass of the β-ZnS nanopowder; the mass proportion of the metal sulfide additive is 0.0wt.% to 5.0wt.% of the total mass of the β-ZnS nanopowder; The precursor powder of zinc sulfide transparent ceramic is placed in a high-temperature sintering mold, hot-pressed and sintered in a vacuum environment or in a protective gas environment, and after cooling, zinc sulfide infrared optical transparent ceramics free of hexagonal wurtzite crystal phase are obtained.

2. The method for preparing a zinc sulfide optically transparent ceramic according to claim 1, characterized in that: The average particle size of the cubic sphalerite crystal phase β-ZnS nanopowder is between 10nm and 100nm.

3. The method for preparing a zinc sulfide optically transparent ceramic according to claim 1, characterized in that: The alkali metal halide salt additive is prepared by mixing one or more alkali metal halide salt powders, which are dried and then mixed and ground into a mixed powder with an average particle size of no more than 300 microns.

4. The method for preparing a zinc sulfide optically transparent ceramic according to claim 3, characterized in that: The alkali metal halide salt is NaBr, NaI, KBr, KI, RbBr, or RbI.

5. The method for preparing a zinc sulfide optically transparent ceramic according to claim 1, characterized in that: The metal sulfide additive is prepared by mixing one or more metal sulfide powders, which are dried, mixed and ground into a mixed powder with an average particle size of no more than 10 microns.

6. The method for preparing a zinc sulfide optically transparent ceramic according to claim 5, characterized in that: The metal sulfide is MgS, CaS, BaS, CaLa2S4, γ-La2S3 or NaLaS2.

7. The method for preparing a zinc sulfide optically transparent ceramic according to claim 1, characterized in that: The specific process of hot pressing and sintering the precursor powder of the zinc sulfide transparent ceramic is as follows: The precursor powder of zinc sulfide transparent ceramic put into the mold is placed in a hot pressing sintering high temperature furnace, and the vacuum degree of the furnace chamber is adjusted to 1.0-20.0 Pa, or argon gas with a flow rate of 30-100 ml / min, or nitrogen gas with a flow rate of 30-100 ml / min is introduced; Applying a pressure of 30MPa to 200MPa to the precursor powder of zinc sulfide transparent ceramic in the mold; The hot pressing sintering high temperature furnace is heated to 750°C to 950°C at a rate of 3 to 20°C / min and kept at this temperature for 0.5 to 3.0 hours; After the heat preservation is completed, the pressure is removed, and after the hot pressing sintering high temperature furnace is naturally cooled to room temperature, the vacuum or Ar gas or nitrogen is removed; The sample is taken out from the mold to obtain a hot-pressed bulk ZnS ceramic, which is polished to obtain a zinc sulfide infrared optically transparent ceramic free of hexagonal wurtzite crystal phase.

8. A zinc sulfide optically transparent ceramic, characterized in that: The zinc sulfide optically transparent ceramic is obtained according to the preparation method of the zinc sulfide optically transparent ceramic according to any one of claims 1 to 7.

9. The zinc sulfide optically transparent ceramic according to claim 8, characterized in that: The raw materials of the zinc sulfide optically transparent ceramic include β-ZnS nanopowder of cubic sphalerite crystal phase with an average particle size of 10nm to 100nm, alkali metal halide salt additives, and metal sulfide additives; the mass proportion of the alkali metal halide salt additive is 3.0wt.% to 7.0wt.% of the total mass of the β-ZnS nanopowder, and the mass proportion of the metal sulfide additive is 0.0wt.% to 5.0wt.% of the total mass of the β-ZnS nanopowder.

10. An application of the zinc sulfide optically transparent ceramic according to claim 8, characterized in that: The zinc sulfide optically transparent ceramic is used as an infrared wave-transmitting material and can transmit long-wave infrared light in the 8-14 μm band.